Analisis Tematik Hadits Tentang Huzn, Ghamm, Dan Ya’s Sebagai Basis Intervensi Depresi Dalam Perspektif Psiko-Spiritual Islam - Agus Suyadi Raharusun; Tias Febtiana Sari; Nara Syarifani (FASTABIQ: JURNAL STUDI ISLAM, 2025)
Depression is one of the mental disorders with a high global prevalence, while pharmacological approaches often fail to address the psychological and spiritual aspects that are at the root of the problem. In Islamic tradition, hadiths contain emotional concepts such as huzn, ghamm, and ya's, which have the potential to form the basis for the development of psycho-spiritual interventions. This study aims to analyze the meanings of these three terms in the hadith of the Prophet and construct a model of Islamic psychological intervention relevant to the treatment of depression. This study employs a thematic-hadith (al-maudhu‘i) qualitative approach, utilizing lafziyah search, takhrij, sanad-matan assessment, and thematic analysis in conjunction with Islamic psychology theory. Of the 30 hadiths that were successfully collected, 5 hadiths passed the criteria of authenticity and relevance. The analysis shows that the hadiths offer three therapeutic interventions: prayer as spiritual-cognitive regulation, talbinah as a biological intervention that affects mood stability, and al-hisā' as aroma-based sensory regulation. All three are consistent with Malik Badri's model of Islamic psychotherapy and Najati's psycho-physiological theory. Hadiths with the themes of huzn, ghamm, and ya's not only describe emotional conditions but also provide a framework for psycho-spiritual interventions that are compatible with modern psychotherapy. This study opens up opportunities for clinical trials of the resulting intervention model.